The Assyrian genocide: cultural and political legacies - Travis, Hannibal (Routledge studies in modern history, 2017)
This book, while principally analyzing the Assyrian genocide of 1914-1925 and its implications for the culture and politics of the region, also raises broader questions concerning the future of religious diversity in the Middle East. A key question is whether the fate of the Assyrians maps onto the concepts used within international law and diplomatic history to study group violence. In this light, and including its Armenian and Greek victims, the Ottoman Christian Genocide rivals the Rwandan and Biafran genocides. Scholars from around the world have collaborated to approach these issues by reference to international legal materials, diplomatic and political archives, and literary works.